การคุ้มครองพื้นที่เกษตรกรรม : กรณีศึกษาพื้นที่การปลูกทุเรียน จังหวัดนนทบุรี (PROTECTION OF AGRICULTURAL LAND: A CASE STUDY OF DURIAN PLANTATION AREA OF NONTHABURI PROVINCE) - อุยยานนท์, พอพันธ์; สัจจานันท์, ศิริพร; โห้ลายอง, ฐิติมา; วนเศรษฐ, อภิญญา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
The objectives of this research were to: 1) analyze the needs of durian farmer, situations and other related factors determining the change and the trend in the land usage for durian cultivation in Nonthaburi province; 2) study the government policy and measures in preservation, rehabilitation and protection for the land usage for durian cultivation and 3) study various appropriate policies and measures in protection and preservation for durian land usage. The research was based on qualitative analysis. The target group was focused on the durian growing farmers in Nonthaburi Province. The key-informant of 309 farmers were selected by stratified random sampling. Various research methodologies were employed including interviews from the field survey including government officials, and the village philosophers academicians, Focus group technique was also undertaken. Various secondary sources were also collected. These were to be mapping for various scenario analysis. Results of the study were shown that: Most farmers still have the need for conservation planting durian. Although it is less profitable to grow durian, they will continue to do this. The future prospects of planting durian was on decline. Three major reasons were as follows. (1) Younger generation tended not to be interested in engaging in this occupation. (2) The high price of land was not worth enough it to use the land to grow durian, and (3) the lack of serious support from the government. The government's measures to promote the conservation and restoration of the durian growers have taken more clearly after the heavy flood took place in 2011. It was operating under the initiative of HRH Princess Sirindhorn. The implementation of the mission were strengthened by the cooperation of various sectors including Ministry of Agriculture and Cooperatives, local authorities, representatives from NGO, These led to the establishments of various Durian Conservation groups in every districts of Nonthaburi Provinces, in order to expanding network of learning and acting as help center and receiving suggestion to government sector. These measures will be more strengthening durian preservation. Various concretes of policies and measures to durian land preservation should be implemented including pilot project by zoning initiated by local community by volunteer in the project, together with offering incentives for durian farmers such as tax measures, reducing cost of production, and the advice of efficient technique of production. If successful, the protection of agricultural land should be expanded.